2019
DOI: 10.1039/c8mt00152a
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent shotgun proteomics revealed distinct effects of an organoruthenium prodrug and its activation product on colon carcinoma cells

Abstract: Time-dependent shotgun proteomics revealed distinct effects of an organoruthenium prodrug and its activation product on colon carcinoma cellsThe unravelling of target interactions in cancer cells is a crucial process for identifying promising metal-based anticancer agents. Therefore, target profiles were analysed in a time-dependent manner using proteomics techniques by accounting for the hydrolysis kinetics of plecstatin, an organometallic ruthenium(arene) derivative. While the intact prodrug provoked a cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 43 publications
1
43
0
8
Order By: Relevance
“…Importantly, α-synuclein (oligomer)-induced ROS production in salt solution or in cells can be blocked by chelators of copper, iron, or zinc [ 22 , 26 ]. This ROS production is less likely to be produced only by transition metals in the medium, because the same medium was used for monomers and fibrils which did not produce ROS and is possibly connected to some structural changes in the α-synuclein molecule induced by these metals ions, although α-synuclein binds these metals in very small amounts [ 27 , 28 , 29 ].…”
Section: α-Synuclein and Oxidative Stressmentioning
confidence: 99%
“…Importantly, α-synuclein (oligomer)-induced ROS production in salt solution or in cells can be blocked by chelators of copper, iron, or zinc [ 22 , 26 ]. This ROS production is less likely to be produced only by transition metals in the medium, because the same medium was used for monomers and fibrils which did not produce ROS and is possibly connected to some structural changes in the α-synuclein molecule induced by these metals ions, although α-synuclein binds these metals in very small amounts [ 27 , 28 , 29 ].…”
Section: α-Synuclein and Oxidative Stressmentioning
confidence: 99%
“…Previous studies showed the target selectivity of plecstatin-1 towards plectin. 10,21 Therefore, we aimed at better understanding whether and how the treatment with plecstatin-1 would impact biological processes in cancer cells. Our work employed multicellular spheroids to further characterize the response of cancer cells upon treatment with plecstatin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of ROS was previously observed for plecstatin-1 in cell culture monolayers. 10,21 Together with a mitochondrial stress signature related to the cytoprotective integrated stress response (ISR), these processes culminated in the phosphorylation of eIF2a. 21 Importantly, eIF2a is a master regulator of several stress response pathways, also including endoplasmic reticulum (ER) stress upon increased ROS, production as part of the unfolded protein response (UPR).…”
Section: Plecstatin-1 Induces Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations